Identifying and filling critical knowledge gaps can optimize financial viability of blue carbon projects in tidal wetlands - Carruthers, Tim J. B.; Jones, S. Beaux; Terrell, Megan K.; Scheibly, Jonathan F.; Player, Brendan J.; Black, Valerie A.; Ehrenwerth, Justin R.; Biber, Patrick D.; Connolly, Rod M.; Crooks, Steve; Curole, Jason P.; Darnell, Kelly M.; et al. (Frontiers in Environmental Science, 2024)
One of the world's largest 'blue carbon' ecosystems, Louisiana's tidal wetlands on the US Gulf of Mexico coast, is rapidly being lost. Louisiana's strong legal, regulatory, and monitoring framework, developed for one of the world's largest tidal wetland systems, provides an opportunity for a programmatic approach to blue carbon accreditation to support restoration of these ecologically and economically important tidal wetlands. Louisiana's coastal wetlands span ~1.4 million ha and accumulate 5.5-7.3 Tg yr -1 of blue carbon (organic carbon), ~6-8% of tidal marsh blue carbon accumulation globally. Louisiana has a favorable governance framework to advance blue carbon accreditation, due to centralized restoration planning, long term coastal monitoring, and strong legal and regulatory frameworks around carbon. Restoration efforts, planned through Louisiana's Coastal Master Plan, over 50 years are projected to create, or avoid loss of, greater than 200,000 ha of wetland. Current restoration funding, primarily from Deepwater Horizon oil spill settlements, will be fully committed by the early 2030s and additional funding sources are required. Existing accreditation methodologies have not been successfully applied to coastal Louisiana's ecosystem restoration approaches or herbaceous tidal wetland types. Achieving financial viability of accreditation of these restoration and wetland types will require updates to existing blue carbon crediting methodologies, or additional methodologies (and/or standards) but is technically feasible. This study identified twenty targeted knowledge needs to address data and knowledge gaps to maximize financial viability of blue carbon accreditation of Louisiana's tidal wetlands. Knowledge needs were identified in five categories: legislative and policy, accreditation methodologies and standards, soil carbon flux, methane flux, and lateral carbon flux. Due to the large spatial scale and diversity of tidal wetlands, it is expected that progress in coastal Louisiana has high potential to be generalized to similar wetland ecosystems across the northern Gulf of Mexico and globally.